Kisah Ashabul Kahfi: Studi Perbandingan Tafsir Al-Misbah dan Tafsir Ibnu Katsir - Muliawann, Juan; Aulia, Widad; Hakim, Luqman Nul (Indonesian Journal Publisher, 2024)
The story is one of the five main contents of the Qur'an, and the stories in the Qur'an are unique and extraordinary. This research will delve into one of the Qur'anic stories, namely the story of Ashabul Kahfi in Surah Al-Kahfi verses 9-26, and compare it with two exegesis books: